The Role of Social Support in Enhancing Psychological Well-Being: The Mediating Effect of Self-Esteem in First-Year University Students - Riski Anda; Nur'aini Nur'aini; Amanah Surbakti (AL-ISHLAH: Jurnal Pendidikan, 2025)
The transition to university life can be stressful for new students, making psychological well-being crucial in overcoming challenges. Social support plays a vital role in psychological well-being, as it influences self-perception and emotional stability. Self-esteem serves as an important mediator in this relationship, where higher self-esteem enhances students' emotional and psychological resilience. This study employed a quantitative research design with purposive sampling, selecting 225 new university students as participants. Data were analyzed using the Structural Equation Model (SEM) with Smart PLS 4.0 to examine relationships between social support, self-esteem, and psychological well-being. Findings indicated that social support significantly influences psychological well-being (β = 0.545, p 0.05) and self-esteem (β = 0.542, p 0.05). Additionally, self-esteem positively impacts psychological well-being (β = 0.332, p 0.05). Mediation analysis confirmed that self-esteem mediates the relationship between social support and psychological well-being (T = 3.713, p 0.05). The study highlights the critical role of self-esteem as a mediator in the relationship between social support and psychological well-being among new students. Strengthening self-esteem through social support mechanisms can enhance students' emotional and psychological well-being, aiding their university adjustment process.